2004
DOI: 10.1080/10256010410001678062
|View full text |Cite
|
Sign up to set email alerts
|

Fish host–cestode parasite stable isotope enrichment patterns in marine, estuarine and freshwater fishes from Northern Canada

Abstract: Cestode parasites from freshwater (threespine stickleback, Gasterosteus aculeatus), estuarine (brook charr, Salvelinus fontinalis) and marine (Greenland cod, Gadus ogac) fish from northern Quebec, Canada, were used to investigate the hypotheses that cestode parasites are (13)C and (15)N enriched relative to host food sources, but (15)N depleted with respect to host muscle tissue as a result of differential enrichment during the assimilation of common nutrient sources. Cestode parasites and fish were generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 25 publications
7
30
0
Order By: Relevance
“…However, our results agree with previous findings that in fish host-parasite systems parasite isotopic signatures referenced to host muscle tissue do not exhibit the conventional pattern of "N and I3C enrichment during the trophic transfer along the food chains ( Fig. I; Pinnegar et al 2001, Deudero et al 2002, Power and Klein 2004. The majority of parasitic cestodes, nematodes, copepods, and isopods showed depleted I' N and 13c with respect to their host fishes.…”
Section: Matefuals and Methodssupporting
confidence: 80%
“…However, our results agree with previous findings that in fish host-parasite systems parasite isotopic signatures referenced to host muscle tissue do not exhibit the conventional pattern of "N and I3C enrichment during the trophic transfer along the food chains ( Fig. I; Pinnegar et al 2001, Deudero et al 2002, Power and Klein 2004. The majority of parasitic cestodes, nematodes, copepods, and isopods showed depleted I' N and 13c with respect to their host fishes.…”
Section: Matefuals and Methodssupporting
confidence: 80%
“…Focken & Becker 1998, Yokoyama et al 2005. Although similar enrichment values have been reported (Table 3), much higher enrichment and depletion values have been previously reported between parasite and host for both ectoparasite-and endoparasite-host systems (Iken et al 2001, Pinnegar et al 2001, Deudero et al 2002, Parmentier & Das 2004, Power & Klein 2004, Persson et al 2007). Accordingly, δ 15 N P -δ 15 N H (P: parasite, H: host) ranged from -4.2 to 2.8 ‰ and δ 13 C P -δ 13 C H from -4.1 to -0.1 ‰ for ectoparasites.…”
Section: Host -Parasite Isotopic Fractionation: Characterization Of Tmentioning
confidence: 48%
“…They have reported that the 'regular' isotopic enrichment of 1 ‰ for δ 13 C and 3 to 4 ‰ for δ 15 N is not the rule (Iken et al 2001, Pinnegar et al 2001, Deudero et al 2002, Parmentier & Das 2004, Power & Klein 2004. However, these studies have examined parasite-host systems with physiological links much weaker than in digenean trematode-mollusc systems and have involved species in other phylogenetic groups than trematodes.…”
Section: Abstract: Parasitism · C and N Stable Isotopes · Marine Molmentioning
confidence: 99%
See 1 more Smart Citation
“…However, important exceptions exist. Fluidfeeders, a group that includes blood-feeding parasites and hempiteran insects (2), frequently have been found to deviate from these typical patterns such that fluid-feeders are usually reported as showing no enrichment or even depletion in 15 N relative to their diet (2,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Although it is now commonly accepted that fluid-feeders deviate from typical patterns of enrichment, these observations have stimulated considerable speculation (2,14,18) but little, if any, research targeted at explaining the mechanistic basis of such atypical patterns of nitrogen enrichment.…”
mentioning
confidence: 99%